Brodalumab efficacy in psoriasis patients with inadequate response to IL-23 or IL-12/23 inhibitors: multicenter Italian retrospective analysis - IL PSO (Italian Landscape Psoriasis) - Orsini, Diego; Fargnoli, Maria Concetta; Burlando, Martina; Campanati, Anna; Campione, Elena; Guarneri, Claudio; Narcisi, Alessandra; Pella, Paolo; Romita, Paolo; Travaglini, Massimo; Zichichi, Leonardo; Arancio, Luisa Maria Halina; et al. (Dermatology Practical & Conceptual, 2025)
Introduction: The use of brodalumab in patients with psoriasis who have failed other biologic drugs is an under-explored topic; A variable percentage of patients still experience primary therapeutic failure, incomplete response, or progressive loss of treatment efficacy (secondary therapeutic failure). In this context, switching treatments among different mechanisms of action has been explored in previous studies conducted on psoriatic patients. However, criteria providing a clear clinical rationale for such transitions are lacking, and no clear guidance is provided by international guidelines to date. Objectives: To evaluate the safety and the efficacy of brodalumab in a subgroup of psoriasis patients who already failed anti-IL23 or anti-IL12/23 treatment. Methods: We retrospectively evaluated, using the PASI and DLQI index, a cohort of 23 patients with psoriasis who underwent a change of therapy with brodalumab exclusively following primary or secondary therapeutic failure of anti-IL-23 or anti-12/23 drugs. Results: The mean PASI decreased significantly following the introduction of brodalumab after 4 weeks of treatment, and continued to decrease at 16 and 36 weeks, reaching the nadir at 52 weeks (baseline PASI baseline= 14.6 ± 9.2 vs. 52 weeks PASI= 1.1 ± 1.8; p <0.001). The 63.6% of patients reached PASI 100 just after 16 weeks. The same trend of improvement was also observed for the DLQI. The adverse effects observed in our study population were generally mild. Conclusions: Our results are in line with the current literature and suggest that patients who have failed therapy with IL-23 or IL-12/23 inhibitors may benefit from switching to brodalumab, which could be considered a good choice for patients who need a rapid resolution of the inflammatory skin condition.